The Role of Parents in Providing Lessons and Sermons on Islamic Educational Ideas from The Perspective of Children in Jordan - AL-Momani, Mohammad Omar (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The study aimed to identify the degree of Parents’ practice of methods of setting examples, lessons, and sermons included in Islamic educational thought from the point of view of university children. This is related to some variables, such as gender, academic specialization, and stage of study, where the researcher followed the Descriptive analytical method. By applying the questionnaire consisting of (15) items, which served as a tool for the study and which was applied to (2500) male and female students from various Jordanian universities in the second semester of the academic year (2023/2024), the study concluded, after conducting appropriate statistical treatments, to the level of parents’ practice of educational methods in general. He came with a degree high on the scale as a whole, with an arithmetic mean of (3.94) and a standard deviation of (0.64). The results also showed that there were no statistically significant differences attributable to the variables of the study, namely the variables of gender (males, females), the variable of the type of student’s academic specialization (scientific, humanities), and the academic stage variable. For students (intermediate diploma and bachelor’s degree). Referring to research findings, it shows that parents have a significant role in providing learning and sermons, guiding them in learning so that children are more focused. Parents use effective advice in the form of short sentences but full of deep meaning.